2021
DOI: 10.1093/jnci/djab122
|View full text |Cite
|
Sign up to set email alerts
|

Association of the COVID-19 Pandemic With Patterns of Statewide Cancer Services

Abstract: The coronavirus disease 2019 (COVID-19) pandemic led to delayed medical care in the US. We examined changes in patterns of cancer diagnosis and surgical treatment between January 1 and December 31 in 2020 and 2019 with real-time electronic pathology report data from population-based Surveillance, Epidemiology, and End Results cancer registries from Georgia and Louisiana. During 2020, there were 29,905 fewer pathology reports than in 2019, representing a 10.2% decline. Declines were observed in all age groups, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
57
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 85 publications
(73 citation statements)
references
References 6 publications
2
57
0
3
Order By: Relevance
“…Modeling studies 43 assuming a 6-month pause in mammography projected a relatively small number of excess BC deaths through 2030, and a 6-month pause in CC screening may lead to a slight stage shift, with minimal impacts on CC outcomes. 44 A recent study 45 of electronic pathology reports showed a 9% decrease in the number of BCs in 2020 compared with 2019, although the stage and outcomes of cancers diagnosed in 2020 and beyond is not yet known. Previous observational studies examining outcomes after the 2009 USPSTF recommendation to lengthen BC screening intervals for women aged 50 to 74 years to every 2 years showed no immediate changes in stage distribution, 46 although screening intervals and practices also did not change.…”
Section: Discussionmentioning
confidence: 99%
“…Modeling studies 43 assuming a 6-month pause in mammography projected a relatively small number of excess BC deaths through 2030, and a 6-month pause in CC screening may lead to a slight stage shift, with minimal impacts on CC outcomes. 44 A recent study 45 of electronic pathology reports showed a 9% decrease in the number of BCs in 2020 compared with 2019, although the stage and outcomes of cancers diagnosed in 2020 and beyond is not yet known. Previous observational studies examining outcomes after the 2009 USPSTF recommendation to lengthen BC screening intervals for women aged 50 to 74 years to every 2 years showed no immediate changes in stage distribution, 46 although screening intervals and practices also did not change.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the overall number of announced cancer diagnosis declined by 9.2% during 2020 compared to 2019, which was in sharp contrast with the consistent yearly growth rates observed during previous years but consistent with the 10.2% decline in pathology reports from a registry based study conducted in two states of the USA. 27 A French multicentric study revealed a similar decline in new cancer cases between March and July 2020, however this did not apply to the whole year. 28 On the contrary, histopathological analyses were roughly comparable between 2019 and 2020 (+2.0%) and rose every month during the pandemic resurgence.…”
Section: Discussionmentioning
confidence: 98%
“…This is likely attributed to diagnostic delays with fewer patients proceeding through routine cancer screening or other diagnostic pathways. 18 These diagnostic delays pose the risk of stage migration, with early data describing a reduction in the reported incidence of early stage cancers with a concurrent increase in stage IV diagnoses among cancers with established screening programs. 19 To account for these potential missing patients, our model simulated patient volumes based on prepandemic cancer surgery volumes.…”
Section: Discussionmentioning
confidence: 99%